2021
DOI: 10.3390/agronomy11061147
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and In Vitro Quality Evaluation of Dual-Purpose Cereals Clipped at Variable Ages and Their Utilization in Rabbit Feeding

Abstract: The present study included two experiments; the first one investigated the forage productivity and in vitro quality of a single cut taken at different plant ages (45, 60, and 75 days after sowing—DAS) from four prominent cereal crops, namely, barley, oat, triticale, and ryegrass, grown during two successive winter seasons in Northern Egypt. In addition, the effect of plant age at forage removal on the crop’s regrowth ability and final grain yield was quantified. The second experiment studied the biological in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Ref. [22] reported similar findings, where they emphasized that the regrowth had higher plant heights at an earlier cutting age. The optimal values were 63, 68, and 50 DAS for plant height, 100-grain weight, and grain yield, respectively.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Ref. [22] reported similar findings, where they emphasized that the regrowth had higher plant heights at an earlier cutting age. The optimal values were 63, 68, and 50 DAS for plant height, 100-grain weight, and grain yield, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…These findings were in agreement with those reported by [23,37,38], who reported that cutting the crop at an advanced age increased the DFY. The increase in DFY may be attributed to the increase in the stem component of the forage and the reduction in the leaf component, where stems are higher in dry matter content than leaves, thus contributing to the DFY of the produced herbage [22]. In addition, as the plant grows the photosynthetic activity increases leading to higher biomass production [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the onset of reproductive growth, grass plants generally show improved regrowth when their foliage is harvested at an earlier stage. During this stage, a substantial amount of the nutrients are retained in the stubble and roots [46][47][48], while the relationship between the time of defoliation and the vigor of regrowth is obscure in winter cereals during the tillering stage [14,49,50]. In this study, defoliation was applied during the reproductive growth stage, and the plants that were mowed earlier exhibited vigorous regrowth.…”
Section: Discussionmentioning
confidence: 89%
“…Regarding carrot's fiber composition, it is constituted predominantly cellulose (80.94% of dry weight), followed by hemicellulose (9.14% of dry weight), pectin (7.41% of dry weight), and lignin (2.48% of dry weight) [16]. Oat hay has high fiber content, which is essential for rabbits' dental and gastrointestinal health; the incorporation of oat hay in rabbit feeding has been previously evaluated with good results once it was concluded that self-production of hay and its inclusion in rabbit feeding was an affordable alternative to optimize the rabbit production costs [17].…”
Section: Introductionmentioning
confidence: 99%